Azithromycin-Chitosan Films for Improved Haemostasis and Wound Healing - Linda Fateh; Susan Waiss; Mohammad Othman (Journal of Pharmacy and Nutrition Sciences, 2019)
Wound healing is a global medical concern, because haemorrhage is still a major cause of morbidity and mortality. Therefore, more effective and cost-effective dressings are required. Antimicrobial dressing of Azithromycin (AZM) (a broad-spectrum macrolide antibiotic) with Chitosan (CS) as a carrier, has a lot of desired properties such as haemostatic, pain-reducing, and less scar forming. It is prepared by a solvent evaporation method. The film morphology is investigated by SEM and film-water wettability is measured by a contact angle method. The drug-polymer interactions are evaluated by using FTIR and DSC. Azithromycin loaded films (different mass ratio of AZM to CS w % 10%, 25% and 50%) were sterilized by Gamma radiation, then their antimicrobial characteristics and haemostatic performance were evaluated. Film thickness was about 9 µm. The wettability properties of films were enhanced by adding AZM and PEG6000 5% (mass ratio of PEG 6000 to CS w %). Microbial growth inhibitions were identified for films loaded with Azithromycin.